Identifying factors that influence participation of farmers in maize marketing in the Highveld region of Eswatini - Karuaihe, Selma Tuemumunu (University of Pretoria, 2022)
Mini Dissertation (MSc (Agricultural Economics))--University of Pretoria, 2022.